Perancangan Website Dinas Pemberdayaan Masyarakat dan Pemerintahan Kampung (DPMPK) Pegunungan Bintang Menggunakan Framework Laravel - Sri Yulianto Joko Prasetyo; Evan Bagus Kristianto (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2021)
In order to cover a wider, efficient and good reach in spreading information, we need the promising technology in order to create a better administration for the government. Dinas Pemberdayaan Masyarakat Kampung (DPMPK) Pegunungan Bintang is trying to use the information technology or IT as a means to spread the information or e-government activity in popular terms. As an effort for realization of its e-government activity, a website with Laravel framework is created using PHP and JavaScript programming language. There are three roles in that website that related to each other. These role are super admin, admin, and a user. The Super Admin and Admin role are divided to minimize unrelated problem to each role and easier to control while changing the website content. DPMPK website is built with simple user interface to make it easy for user while browsing some information and to download the required documents.